EDUKASI JAJANAN SEHAT PADA ANAK USIA SEKOLAH DI PONDOK PESANTREN BAITUL QURAN AL-IKHWAN - Millah, Izzatu; Handayani, Putri; Veronika, Erna (LPPM Universitas Bina Bangsa, 2025)
Snacks have a significant role in the energy and nutrient intake of school-age children. School-age children have a penchant for consuming excessive amounts of different types of food. However, school snacks that are less guaranteed health can have risks that can cause digestive disorders, poisoning, and if it lasts for a long time can lead to poor nutritional status. This activity aims to increase students' knowledge through education about the importance of healthy snacks. This activity was carried out at the Baitul Quran Islamic Boarding School Al-Ikhwan Jakarta, on Saturday, 25 May 2024. Activities in the form of counselling about the importance of healthy snacks. To evaluate this educational activity, a questionnaire in the form of closed questions was given to students before and after education. The results of the activity showed that there was an increase in student knowledge about healthy snacks when compared between before (66.85%) increased to (92.27%) after education. This activity is expected that the nutrition education provided can improve nutritional knowledge and healthy snacking behaviour so as to create optimal nutritional status.